FAKTOR-FAKTOR YANG MEMENGARUHI BELUM DIAPLIKASIKANNYA AKAD SALAM PADA PERBANKAN SYARIAH (Studi Pada 3 BPRS Yogyakarta) DAN KAITANNYA DENGAN PENGURANGAN TINGKAT KEMISKINAN - MUHAMMAD AKHYAR ADNAN, NERY REVISA (FE UMY, 2012)
This research aims at identiying the factors which caused the un-applicability of salam product in Islamic Banks. This is important to note because it might be directly or indirectly related to poverty eradication, as Islamic banks are expected to help the poor and needy parties, particulary those are from the agribusiness background society. This research applies the descriptive and exploratory approach. Objects in this research are three Rural Financing Sharia Banks (RFSB â€“ BPRS), they are â€œBangun Drajat Wargaâ€, â€œMitra Amal Muliaâ€, and â€œBarakah Dana Sejahteraâ€. The subjects of researech consist of three group of people, these include experts (selected lecturers in UMY), bankers, and customers of Rural Financing Sharia Banks. The results show that there are several factors which have caused the un-applicability of product Salam. They are a high risk, no demand, limited human resources, low or lack of public understanding, and the complicated application. Further examination using different approach seems to be interesting to note.